Madecassoside Inhibits Body Weight Gain via Modulating SIRT1-AMPK Signaling Pathway and Activating Genes Related to Thermogenesis - Sun, Boju; Hayashi, Misa; Kudo, Maya; Wu, Lili; Qin, Lingling; Gao, Ming; Liu, Tonghua (Frontiers in Endocrinology, 2021)
Background: Madecassoside (MA) is a pentacyclic triterpene saponin that is obtained from Centella asiatica and possesses a wide variety of pharmacological activities. Pre-clinical research studies have shown that MA has favorable therapeutic effects on arthritis, acne, vitiligo and other diseases. However, the effects of MA on obesity have not yet been studied. This study mainly aimed to investigate the effects of MA in protecting against obesity and its underlying mechanism in reducing obesity. Methods: Obese diabetic KKay/TaJcl mice model were randomly divided into two groups: control group (n=8), wherein the mice were given water, and MA group (n=8), wherein the mice were given MA (40mg/kg/day). The body weight of all animals was recorded daily during the initiation of the experiment and they were given single doses of MA through oral gavage daily for 8 weeks. The blood glucose, blood lipid, and serum aminotransferase levels were examined at weeks 4 and 8, respectively. The expression of P-AMPK, SIRT1, P-LKB1, P-ACC, and P-HSL in abdominal fat, mesenteric fat and epididymal fat was measured by western blotting, and the levels of PPARα, CPT1, PGC-1α, UCP-1, Cidea, Cox7a1, and Cox8b were examined by real-time quantitative PCR (RT-qPCR). Results: The results revealed that the body weight of the mice in MA group was significantly reduced, and the body mass index (BMI) showed significant difference between the two groups after 8 weeks of MA treatment. Further research revealed that it affected the mesenteric fat and epididymis fat by activating SIRT1/AMPK signaling pathway, and then promoted fatty acid oxidation of epididymal fat (PPARα , CPT1, and PGC-1α). Last but not the least, it also promoted the expression of UCP-1 and stimulated thermoregulatory genes (Cidea, Cox7a1, and Cox8b) in brown fat and mesenteric fat. Conclusions: Taken together, these findings suggest that MA can inhibit the weight gain in obese diabetic mice, and reduce triglyceride levels, inhibit lipogenesis of mesenteric fat, promote epididymal fat lipolysis and fatty acid oxidation. Furthermore, MA treatment might promote mesenteric fat browning and activate mitochondrial function in brown fat as well as mesenteric fat.